PEMBENTUKAN SELF CONTROL SISWA MELALUI MATA PELAJARAN AQIDAH AKHLAK (Studi Kasus Kelas XI MA Bahrul Ulum Besuk) - M. Thufail Muttaqin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
The importance of an educator through education to be able to form student self-control is an effort to overcome all adolescent problems that occur at school age, especially at MA Bahrul Ulum. Therefore, the authors are interested in conducting research with the title Formation of Student Self Control through Aqidah Akhlak Subjects (Case Study of MA Bahrul Ulum Besuk Probolinggo) "The focus of the research consists of three, namely: 1. How is the Self Control of Class XI MA Bahrul Ulum students through Aqidah Akhlak Subjects? 2. How are the efforts of the Aqidah Akhlak Subject Teacher in the formation of self-control for class XI MA Bahrul Ulum students? 3. What are the supporting and inhibiting factors for the formation of Student Self Control through the Aqidah Akhlak class XI MA Bahrul ulum?. The research approach used in this research is a qualitative approach (qualitative research). Based on the data obtained in the field, the Self Control that occurred at MA Bahrul Ulum was not very good. Therefore, it is necessary to establish Student Self Control through Aqidah Akhlak Subjects as an urgent urgency in order to form students who are able to control themselves.